Strategies to overcome challenges when implementing an Enterprise Engineering Innovation Life-cycle - Du Toit Francois (Department of Information Systems, 2019)
The delivery of innovative IT solutions that support business strategy is an increasing, growing competitive aspect of organisations in the financial sector. Previous research has shown the need to follow an innovative or a more agile and flexible methodology when delivering IT solutions to save cost and enable the solutions to reach the consumer market as soon as possible. To apply agile/innovative methodologies across large organisations requires more alternative approaches than to implement them in small enterprises. The organisation used in the case study, implemented an enterprise engineering innovative lifecycle (EEILC). Limited research has been done concerning the challenges and strategies during implementation of an EEILC. The purpose of this study was to investigate the strategies to overcome the challenges when implementing an EEILC. The research was inductive qualitative following an in-depth case study approach. The researcher conducted a case study using documentation analysis, informal interviews, in-depth interviews and observations with multiple stakeholders who are experts in their fields of software design and development. An inductive grounded theory approach was followed using a case study within an organisation in the financial sector in South Africa. Results show there are seven core category challenges when implementing an innovation life cycle. Each of these core challenges has a core enterprise strategy to address the challenges occurring in the applicable domain. The core challenges are: (1) innovation process challenges (addressed by an agile product delivery innovation strategy) (2) invention challenges (addressed by an idea management strategy) (3) business model challenges (addressed by a client’s value proposition strategy), (4) commercialization challenges, which include implementation and operations challenges, (addressed by a product portfolio management strategy), (5) culture challenges (addressed by an innovation culture strategy) and (6) knowledge management challenges and strategy, and (7) innovation management related challenges and strategy An innovation management strategy will manage all these challenges. Most prominent is the innovation management strategy which has links to all other categories in other domains. The relationship between enterprise client value proposition strategy show that enterprise client value proposition serves as a coherent link between how the innovation life cycle is adopted or changed to address the enterprise client value chain. This is driven by demand management to align between business and IT regarding the business model and application portfolio alignment. Thereafter, the alignment between the demand for enterprise application capabilities and the business service portfolio is shown. This is supported by service-oriented architecture (SOA) services. The resource management has to make sure the right resources, competencies and skills are available to deliver the product portfolio. During innovation and life-cycle's execution, there is a lot of interaction between individuals and teams. Therefore, communication and culture play a vital role to create synergies by collaboration of work practice and living the values of the organization. Through grounded theory analysis, a practical theory was developed, to show how challenges that occur during implementation of an innovation life-cycle, based upon enterprise engineering principles, can be addressed by best by putting the right strategies in place. This theory contributes to the body of knowledge by providing data and analysis from practical insight into how an innovation life cycle can be implemented. The challenges thereof and the mitigating strategies make it work. This study also suggested the key re best practices for enterprise architecture driving such an implementation. The research is an area of interest for development or customizing an Innovation Life-cycle using an Enterprise Engineering Framework.